Study on the performance of glazed hollow bead insulation mortar for high temperature mine roadway - Yueping Qin; Qiang Liu; Mingyan Guo; Fei Tang; Hairong Wang (Case Studies in Thermal Engineering)
As the mining operations progress into the stages of deep excavation, heat dissipation from the high temperature surrounding rock makes the problem of heat damage more and more serious. The application of insulation mortar effectively restricts the heat transfer between high temperature rock and airflow, which is of significant importance for ensuring safe production of deep mines. In this paper, the effects of aggregate gradation, aggregate-to-cement ratio (a/c) and water-to-cement ratio (w/c) on the performance of glazed hollow bead (GHB) insulation mortar were studied by designing an orthogonal experiment. Based on the experimental results and the analysis of efficiency coefficient, the mix ratio of the thermal insulation mortar with the best comprehensive performance was obtained. Finally, a model for predicting airflow temperature in actively insulated mine roadways was established, and the application effectiveness of insulation mortar under various work circumstances was investigated. The findings indicate that the thermal conductivity (λ) of the mortar specimen with the best comprehensive performance is 0.2172 W/(m·K), and the relative content of GHB composite aggregate in the mortar is about 22 %. The outlet airflow temperature of a 1000 m roadway can be reduced by 6.25 °C at the optimum thickness of 0.2 m.